The Impact of TikTok on Changing Partner Selection Standards for Indonesian Women - Chris Steven Sado Fodhe Au (International Journal of Science and Environment (IJSE), 2026)
TikTok is one of the social media platforms with the most users globally, with a total of 1.94 billion users as of July 2025, and Indonesia is the country with the largest number of TikTok users, with a total of 194 million users as of July 2025. Indonesian TikTok users are dominated by women with a percentage of 50.8 percent and men 49.2 percent. The influence of the development of the social media world has had a significant influence on the formation of partner standards. The purpose of this study is to examine and analyze how TikTok influences partner selection standards among Indonesian women. The study was conducted using the Qualitative Content Analysis (Qualitative Content Analysis) or Netnography method. The method of analysis includes observation of viral videos or analysis of the comment column on certain accounts. The results show that Indonesian women have experienced a significant shift in partner selection standards due to exposure to TikTok content. These findings identify an increase in expectations focused on aspects of economic stability, having a high-income job, and meeting comprehensive emotional needs through the concept of the five love languages. Furthermore, these standards include demands for the absolute availability of material resources, time, and energy from men without any demands for balanced reciprocity in the relationship. TikTok's influence plays a role in determining women's criteria, which requires men to provide all of a woman's needs, both physical and spiritual, as well as other basic needs.